Effect of Blanching and Ultrasound on Drying Time, Physicochemical and Bioactive Compounds of Dried Cashew Apple - LAGNIKA, LATIFOU (My University, 2019)
In the present study, the influence of ultrasound (US) and blanching (BL) compared to untreatment (UN) on the drying rate, color, rehydration, total phenolic content, antioxidant activities and sensory evaluation of cashew apple were investigated. Ultrasound dehydration of cashew apple followed by BL, respectively, showed the faster drying time compared to UN. Ultrasound treatment was effective in retaining on whiteness of dried cashew apple. The color difference of US followed by BL was significantly lower (p<0.05) compared to UN samples. Ultrasound caused a higher retention of total phenolic and flavonoids content and presented the highest antioxidant power. It emerged from this study that ultrasound can be employed successfully as pretretment prior to dried cashew apple with better nutritional attributes.
Keywords: ultrasound; blanching; drying; cashew apple; bioactive compounds